SIMPLE METHOD FOR DIGITAL DATA RECORDING OF DAMPED OSCILLATIONS OF MECHANICAL PENDULUM - TODICA, M.; POP, C. V. (Studia Universitatis Babeș-Bolyai Physica, 2017)
A simple method for digital data acquisition of low frequency damped oscillations of mechanical pendulum is proposed. The method use very simple equipment available in every didactic laboratory. It is intended for didactic purpose, but the method can be used for scientific investigations also.